The productive accountant as (un-)wanted self: Realizing the ambivalent role of productivity measures in accountants' identity work - Goretzki Lukas; Pfister Jan A. (Elsevier (Commercial Publisher), 2022)
How do accountants experience and respond to increasing productivity pressure and a corresponding measurement regime monitoring their work? Drawing on case research in an international technology company, our study problematizes that productivity measurement tends to build on the assumption that accountants perform primarily routinized and standardized tasks that are amenable to quantification. However, this assumption can contradict their business partner identity, which they perceive as entailing complex, varying, and strategically oriented tasks that are difficult to measure and evaluate in standardized units. We find that accountants’ realization of this ambiguity in productivity measurement can make them recognize the (potential) unwanted self that an unreflective subordination to those measures might give rise to. We further illustrate how, to protect their aspired identity against the entrenchment of such an unwanted self, accountants (subtly) resist productivity measures. We thus show how accountants resist the very technologies that otherwise form their tools of the trade and shape a crucial part of their occupational identity and status. Overall, by focusing on the ambivalent role of productivity measurement, this study contributes to our understanding of the organizational dynamics that make accountants’ business partner identity fragile. We demonstrate how productivity measures can produce a false sense of clarity and direction and an incomplete representation of an occupational identity, which also renders problematic the transparency and comparability that those measures produce.